Penguatan Pembelajaran Sistem Daring - Ahmad Taufik; fitriyani fitriyani (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2020)
The learning process is a process control that contains a series of teacher and student implementations on the basis of reciprocal relationships that take place in educational situations to achieve certain goals. This reciprocal interaction between teachers and students is the main condition for the learning process to take place. In reality we see in schools, teachers are often too active in the learning process, while students are made passive, so that the interaction between teachers and students in the learning process is ineffective. If the learning process is dominated by teachers, the effectiveness of learning will not be achieved. To create effective learning conditions, teachers are required to be able to manage the learning process that provides stimulation to students so that they are willing and able to learn.However, learning online is not as easy as we imagine. Many students and teachers encounter obstacles due to stuttering with this online learning. Teachers who could not teach directly encountered obstacles even though the activities were carried out by means of video calls. Many school materials given to students are difficult to understand because of the many distractions when carrying out activities. The problem is generally because the subject matter is the lesson that must be exemplified face-to-face, if this is constrained because it is not direct, it is like a child is wrong and is disturbed by signals, the material also cannot be conveyed properly.